Preparation and Characterization of Ni-Based Perovskite Catalyst for Steam CO2 Reforming of Methane - Yang, Eun-Hyeok; Kim, Sang Woo; Ahn, Byong Song; Moon, Dong Ju (AMER SCIENTIFIC PUBLISHERS, 2013)
Steam CO2 reforming of methane was investigated over Ni-based perovskite catalyst to produce desired H-2/CO ratio by adjusting the feed ratio of CH4, CO2 and H2O for floating GTL process application. La modified perovskites were prepared by the Pechini method and calcined in air and the Ni-based catalysts were prepared by dispersing Ni on the La modified perovskite by an incipient wetness impregnation. The catalysts before and after the reaction were characterized by N-2 physisoprtion, CO chemisoprtion, XRD, TPR and SEM techniques. To control desired H-2/CO ratio, simulation for SCR was carried out by Aspen plus, and product distribution for SCR was investigated in a fixed bed reactor system using feed ratio estimated by simulation. The Ni-based perovskite catalysts were found to give CH4 and CO2 conversions of up to 82% and 60% respectively to yield a H-2/CO product ratio close to 2.
Keywords: LANIO3 PEROVSKITE